In vitro activity of the essential oil from Hesperozygis myrtoides on Rhipicephalus (Boophilus) microplus and Haemonchus contortus - Castilho, Caroline V. V.; Fantatto, Rafaela R. [UNESP]; Gainza, Yousmel A.; Bizzo, Humberto R.; Barbi, Nancy S.; Leitao, Suzana G.; Chagas, Ana Carolina S. (Soc Brasileira Farmacognosia, 2017)
Commercial antiparasitics have been the main tool to control parasites, but due to the resistance development, plant extracts have been widely investigated to find new molecules. The present study aimed to investigate the in vitro acaricide and anthelmintic activities of the essential oil from the aerial parts of Hesperozygis myrtoides (A.St.-Hil. ex Benth.) Epling, Lamiaceae. The essential oil was obtained by hydrodistillation analyzed by GC-FID and GC-MS. Four tests were conducted in vitro to screen the antiparasitic action of the essential oil. The evaluation on Rhipicephalus (Boophilus) microplus was performed with the adult immersion test at concentrations ranging from 0.391 to 25 mg/ml and the larval packet test from 3.125 to 100 mg/ml. For Haemonchus contortus the egg hatch test was performed from 0.012 to 25 mg/ml and the larval development test from 0.003 to 0.4 mg/ml. The LC50 and LC90 values were calculated by Probit. The main components identified in the essential oil were isomenthone (47.7%), pulegone (21.4%), limonene (7.7%), isomenthyl acetate (6.8%) and neoisomenthol (3.9%). In the larval packet test the LC50 and LC90 were 13.5 and 21.8 mg/ml, respectively. In egg hatch test, the LC50 and LC90 were 0.249 and 0.797 mg/ml, respectively, while in the larval development test were 0.072 and 0.167 mg/ml, respectively. This is the first report of the H. myrtoides evaluation against those parasites. The anthelmintic results proved its efficacy on H. contortus encouraging new research with a focus on their main bioactives. (C) 2016 Sociedade Brasileira de Farmacognosia. Published by Elsevier Editora Ltda. This is an open access article under the CC BY-NC-ND license.
Keywords: Phytotherapy; Medicinal plants; Essential oils; Pulegone; Acaricides; Anthelmintics